Borges as Translator - Sarah Simpson (Forum, 2019)
Jorge Luis Borges, primarily known for his original short fiction, also published many translations of other authors’ works over the course of his life, as well as essays on translation theory. Borges proclaimed his own ‘periphrastic’ approach to translation, taking the opportunity to effect changes in his versions of other writers’ works rather than simply attempting to render the source texts into Spanish. In order to examine the strategies employed by Borges in his translations of English-language prose fiction, this paper will consider three texts translated by Borges alongside the original versions: “The Red-Headed League” by Arthur Conan Doyle, and Edgar Allan Poe’s “The Facts in the Case of M. Valdemar” and “The Purloined Letter.” Analysis of these texts will demonstrate the extent to which Borges is prepared to put into practice the theory of radical innovation that he outlines in his essays on literary and translation theory.